Analysis of macroeconomic determinants of peruvian gold export value in the period 2003-2019 - Tovar Jaco, Carlos Alberto (2021)
The current research examined the macroeconomic determinants of Peruvian gold exports in the period 2003-2019 as well as their relative importance. Regressors employed were inflation, exchange rate, international rate, interest rate and Swiss gross domestic product. Ordinary Least Square along with decomposition and standardized coefficients were employed. The research found positive effects of inflation and international gold price on the dependent variable; while, Swiss gross domestic product was found to have a negative effect to Peruvian gold export. By the usage of decomposition and standardized coefficients it was found that international gold price is the most relevant regressor when explaining Peruvian gold export values.